2013
DOI: 10.1111/1462-2920.12232
|View full text |Cite
|
Sign up to set email alerts
|

The Trojan Horse of the microbiological arms race: phage‐encoded toxins as a defence against eukaryotic predators

Abstract: Phage-encoded Shiga toxin (Stx) acts as a bacterial defence against the eukaryotic predator Tetrahymena. To function as an effective bacterial anti-predator defence, Stx must kill a broad spectrum of predators. Consistent with that assertion, we show here that bacterially encoded Stx efficiently kills the bacteriovore Acanthamoeba castellanii in co-culture. We also show that, in addition to Stx, the phage-encoded exotoxin, diphtheria toxin (Dtx) expressed by Corynebacterium diphtheriae also can function as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 57 publications
3
53
1
Order By: Relevance
“…This sacrifice of a small percentage of cells produces sufficient Stx to kill eukaryotic unicellular predators and warrants survival of the remainder of the population (33). Protozoa kill their bacterial prey with reactive oxygen species; oxidative stress also induces Stx production as a self-defense mechanism for STEC (33,34). H 2 O 2 (2.5 mM) induced the expression of Stx2 and production of the Stx2-phage by a small percentage of the population (this study).…”
Section: Discussionmentioning
confidence: 60%
“…This sacrifice of a small percentage of cells produces sufficient Stx to kill eukaryotic unicellular predators and warrants survival of the remainder of the population (33). Protozoa kill their bacterial prey with reactive oxygen species; oxidative stress also induces Stx production as a self-defense mechanism for STEC (33,34). H 2 O 2 (2.5 mM) induced the expression of Stx2 and production of the Stx2-phage by a small percentage of the population (this study).…”
Section: Discussionmentioning
confidence: 60%
“…Many microbes secrete toxins that improve ecological conditions for the producer (Driscoll, Espinosa, Eldakar, & Hackett, ), acting either as antibiotics, impairing or eliminating microbial competitors and thereby reducing competition for limited resources (Chao & Levin, ; Driscoll et al., ; Pierson & Pierson, ) or as virulence factors that allow host invasion, paving the way for colonization and access to new/richer environments (Raymond, West, Griffin, & Bonsall, ). Previous studies showed that Shiga toxin (Stx), a bacteriophage‐encoded exotoxin, can kill bacterivorous single‐celled protist predators (Arnold & Koudelka, ; Lainhart et al., ; Steinberg & Grinstein, ; Stolfa & Koudelka, ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, bacteria in all phyla have developed an array of antipredator defense strategies. Our earlier investigations demonstrate that Shiga toxin (Stx) encoding bacteriophage in E. coli can provide a bacterial population with the ability to combat predation by phagocytic predators (Arnold & Koudelka, ; Lainhart, Stolfa, & Koudelka, ; Mauro, Opalko, Lindsay, Colon, & Koudelka, ; Stolfa & Koudelka, ). We also showed previously that in the face of attack by predator, a only minor subset of bacteria lysogenized with temperate Stx‐encoding lambdoid phage produce and release sufficient exotoxin to substantially reduce of predation the balance of the (Arnold & Koudelka, ; Lainhart et al., ; Stolfa & Koudelka, ).…”
Section: Introductionmentioning
confidence: 99%
“…In other protists, bacteria sometimes can survive and reproduce in phagocytic vesicles and also can produce toxins for killing the host [67,68] and after that for infecting the organism containing the protozoon. This is why Tetrahymena infection is very dangerous to many fish species [69].…”
Section: Discussionmentioning
confidence: 99%